Sepsis Survivors Transitioned to Home Health Care: Characteristics and Early Readmission Risk Factors. - Bowles, Kathryn H. (J Am Med Dir Assoc, 2019)
Findings present key risk factors for early readmission among sepsis survivors transitioning from acute care to HHC and indicate the need to affirm the presence of a sepsis diagnosis and risk factors across settings.